Association Between Inter-Agencies Cooperation and Border Governance of Nepal - Upreti, Yukesh (Journal of APF Command and Staff College, 2023)
Border agency cooperation is the process by which different agencies joins together for the purpose of attaining a common goal in building efficiencies for facilitating international trade, cross border travel by improving cross border security. The government of Nepal has established different agencies to enhance border governance. The purpose of this article is to analyze the relationship between inter-agency cooperation and border governance of Nepal. The research follows a sequential explanatory research design using primary and secondary data. Primary data are extracted from stratified sampling technique using five point likert-scale questionnaires where 202 responses were acquired. The findings show that there is a positive relationship between independent variables of inter-agencies cooperation and border governance of Nepal. Furthermore, inter-agency cooperation and border governance have a positive correlation coefficient of 0.391 at 1 percent level of significant. The regression analysis show interagency cooperation has 30 percent effect in border governance of Nepal. The beta value shows one unit of change in inter-agency cooperation will bring 0.523 unit of change in border governance of Nepal. The study suggest on enhancing information, intelligence & data exchange program on daily basis and improvement on mutual negotiation, synchronized border inspection, and mutual trust within the border governing agencies for maintaining good border governance of Nepal by enhancing service delivery.